Digital Marketing Strategy of Heavy Equipment Rental Services During the COVID-19 Pandemic - Putra Bhagaskara, Dwiki; Alexander, Aldy; Nur Aziz, Muhammad; Lukiyanto, Kukuh (KnE Social Sciences, 2024)
This study aimed to find the right marketing strategy for the business of selling heavy equipment rental services during the COVID-19 pandemic. The research method used was qualitative. Data collection was carried out through interviews with all employees of CV Aneka Tractors. The data analysis process used an analysis tool, namely Nvivo 12 Pro to obtain factors that influenced both internal conditions and strategic steps taken by CV Aneka Tractors. The results of the research showed that CV Aneka Tractors, which initially focused on working on government projects (B2G) and private projects (B2B), had to switch to the individual/community sector (B2C). The B2C sector was an open opportunity during the COVID-19 pandemic. The results showed that during the COVID-19 pandemic, not all consumer sectors were able to make the best contribution, especially in the heavy equipment rental service industry. With a strategy of shifting the target focus to the B2C sector by adjusting the pattern of services offered, establishing cooperation and reducing payment deadlines, companies can survive. From this research, we also saw how important marketing planning is in keeping the company operating. Keywords: management, business, marketing strategy, SWOT analysis